An Overview of the Trends of Road Accidents and Indices in Nepal - Tharu, Nanda Kumar; Shrestha, Yogesh Man (NUTA Journal, 2021)
This paper discusses the current state of accidents with reference to variety of factors. Of years 2068 to 2076, secondary data was picked up from Kathmandu’s metropolitan traffic police division. Trend and Statistical Analysis has been used. Seasonal indices has been calculated to examine time-effect on accidents rate. Numerous element were responsible to road accidents that contributes to the occurrence of accidents in its own way, and there may be many additional situation-specific factors untapped. However, the bulk of road traffic accidents have been seen in drivers age between 21 to 40, types of vehicles reported on accidents were motorcycles, scooters, tractors, and tempos, and , time between the hours of 6 p.m. and 12 a.m. Similarly, male pedestrians and motorcyclists/scooters had a higher rate of fatality. The hours of 12 p.m. to 6 p.m. had 17.8 percent more accidents than average, and the hours of 6 p.m. to 12 a.m. had a 68.15 percent higher chance of an accident.